Analisis Yuridis Pengesahan Jual Beli Tanah Di Bawah Tangan Dan Implikasinya Terhadap Balik Nama Sertipikat Hak Guna Bangunan (Studi Putusan Nomor 132/Pdt.G/2025/PN.Srg) - Amin Rahmat Sidik; Ahmad Rizky Apriana (CV. Kurnia Grup, 2026)
In Indonesia’s agrarian legal system, every transfer of land rights must be registered to ensure legal certainty and protection. However, private land sale transactions conducted without the involvement of a Land Deed Official (PPAT) remain common. This study analyzes the legal validity of such transactions, judicial considerations in related disputes, and their implications for land administration. Using a normative juridical method with statutory and case approaches, this research examines Decision Number 132/Pdt.G/2025/PN.Srg. The findings show that private land sales are substantively valid if they meet the requirements of Article 1320 of the Indonesian Civil Code. Nevertheless, they lack formal administrative validity because they are not supported by an authentic PPAT deed and therefore cannot serve as a basis for registering the transfer of land rights. In the examined case, the court applied a substantive justice approach by considering the purchaser’s good faith, long-term possession of the land, and supporting evidence. As a result, the court decision functioned as a legal substitute for the sale and purchase deed, enabling the transfer of the land certificate. This study highlights the important role of courts in bridging the gap between formal legal requirements and social realities while promoting legal certainty and justice in land administration.